Analisis Penggunaan Biaya Diferensial dalam Pengambilan Keputusan Manajerial - Geby Oktavia Tampubolon; Kisniah Samosir; Debora Fransiska; Hamonangan Siallagan (CV. Ulil Albab Corp, 2024)
This study explores the analysis of the use of differential costs in managerial decision making using secondary data. The results of the case study show that differential cost analysis influences and improves the effectiveness and efficiency of decisions, such as the decision to accept special orders, choosing whether the company produces itself or buys from outside, and investment decisions. The findings are consistent with the literature and support the importance of differential cost analysis in management. Limitations of this study include reliance on secondary data and potential bias in document selection. Managerial implications include using relevant cost information to make more effective decisions. This study recommends analysis across different industries and improved secondary data collection methods for further research.